Does a tiger go to the dentist? : think about how teeth stay healthy - Ziefert, Harriet (Blue Apple Books, 2014)
"The ways animals and people use and keep their teeth healthy are explored in this title in Blue Apple's Think About...series. By contrasting the behavior of people and animals, the series helps young children understand what makes humans, and themselves, unique."--